Uganda : Technical Assistance Report-Report on the Monetary and Financial Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses the technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding mapping of source data for savings and credit cooperatives to the IMF's Standardized Report Form 2SR. The IMF mission's recommendations are aimed at improving the collection and compilation of monetary statistics for other depository and financial corporations based on the Monetary and Financial Statistics Manual (MFSM). The compilation of monetary statistics and the expansion of its institutional coverage based on the MFSM will improve data quality and usefulness for policy analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet